STRATIGRAPHY OF THE HOLE COMALCALCO NO 2 IN TABASCO - ALVAREZ, JAVIER A (Instituto Politécnico Nacional, Escuela Nacional de Ciencias Biológicas, CD MEXICO, DF, MEX, 1950)
Foraminifers are listed from the L, M, and U Miocene
BOL ASOC MEX GEOL PET
Keywords: STRATIGRAPHY, COMALCALCO, TABASCO; CIENCIAS DE LA TIERRA Y DEL ESPACIO; GEOLOGIA; ESTRATIGRAFIA